2016
DOI: 10.1038/aps.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

Tolterodine reduces veratridine-augmented late INa, reverse-INCX and early afterdepolarizations in isolated rabbit ventricular myocytes

Abstract: Aim: The augmentation of late sodium current (I Na.L ) not only causes intracellular Na + accumulation, which results in intracellular Ca 2+ overload via the reverse mode of the Na + /Ca 2+ exchange current (reverse-I NCX ), but also prolongs APD and induces early afterdepolarizations (EAD), which can lead to arrhythmia and cardiac dysfunction. Thus, the inhibition of I Na.L is considered to be a potential way for therapeutic intervention in ischemia and heart failure. In this study we investigated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Among the cardiac ion channels found to be targets of tolterodine, hERG channel exhibited the highest sensitivity (IC 50 of 17 or 9.6 nM when overexpressed in mammalian cells) compared with Na + channel (no effect at 1 μM in overexpression system; IC 50 of 32.08 nM for late Na + current in rabbit ventricular myocytes) and L-type Ca 2+ channel (IC 50 of 143 and 1084 nM in guinea pig ventricular myocytes). 18,19,43 In clinical practice, tachycardia and palpitations have been observed after use of tolterodine. 44 Because the inhibitory potency of tolterodine on hERG channel is similar to that on muscarinic receptors, 1 both pharmacological mechanisms may contribute to its potential to increase heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cardiac ion channels found to be targets of tolterodine, hERG channel exhibited the highest sensitivity (IC 50 of 17 or 9.6 nM when overexpressed in mammalian cells) compared with Na + channel (no effect at 1 μM in overexpression system; IC 50 of 32.08 nM for late Na + current in rabbit ventricular myocytes) and L-type Ca 2+ channel (IC 50 of 143 and 1084 nM in guinea pig ventricular myocytes). 18,19,43 In clinical practice, tachycardia and palpitations have been observed after use of tolterodine. 44 Because the inhibitory potency of tolterodine on hERG channel is similar to that on muscarinic receptors, 1 both pharmacological mechanisms may contribute to its potential to increase heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that veratridine prolongs AP duration in rabbit ventricular myocytes47. Although inactive on hERG channels, alfuzosin produces LQT syndrome in the clinic due to its ability to increase the peak current of Nav1.548.…”
Section: Discussionmentioning
confidence: 99%
“…We also noted an APD reverserate dependence (RRD) in these experiments ( Figure 1D and 1C). However, 100 and 200 μmol/L barbaloin decreased the APD 90 at the frequencies of 0.5, 1 and 2 Hz by 15.1%±3.4%, 12.9%±3.2% (n=8, P>0.05 vs 0.5 Hz), and 9.6%±2.5% (n=8, Effects of barbaloin on ATX II-induced APD prolongation and EADs, as well as Ca 2+ -induced DADs It has been reported that enhanced I Na.L causes APD prolongation and EADs in various pathological conditions [15,16] . ATX II, an I Na.L opener, significantly enhanced I Na.L and thus significantly increased the incidence of APD prolongation and EADs in the ventricular myocytes (Figure 2A and 2C).…”
Section: Effects Of Barbaloin On Apsmentioning
confidence: 99%
“…Effects of barbaloin and TTX on I Na.L I Na.L is generally known as a TTX-sensitive current that is almost completely blocked by 4 μmol/L TTX [16] . The amplitude of the current enhanced by 10 nmol/L ATX II was decreased to almost zero after the administration of 4 μmol/L TTX ( Figure 5A).…”
Section: Effects Of Barbaloin On I Calmentioning
confidence: 99%